Cinema Brasileiro Contemporâneo e Subalternidade: Impasses da Representação - Prates de Oliveira, Marinyze das Graças (Brasiliana: Journal for Brazilian Studies, 2013)
Resumo: Este artigo busca refletir sobre a emergência, no cinema brasileiro produzido nas duas últimas décadas, de um expressivo número de filmes que tematizam a questão da subalternidade. Priorizamos aqui a análise de Uma onda no ar (Helvécio Ratton, 2002), com a finalidade de examinar os impasses da representação de comunidades periféricas — situadas nas margens da nação — pela cinematografia contemporânea. Abstract: This article aims to reflect about the emergency of an expressive number of Brazilian films, produced during the last two decades, which thematize the question of subalternity. We prioritize here the exam of Uma onda no ar, directed by Helvécio Ratton (2002), in order to analyze the impasses that involve the representation of peripheral communities — located in the borders of the nation — by the contemporaneous cinematography.